Politeness strategies used in “Taylor Swift's songwriting process on Evermore" interview - Ramadhanti, Dinda Aulia; Andriani, Diyah Iis (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2024)
The objective of this study was to find out the types of politeness strategies and the factors that influence their use in a video interview between Zane Lowe and Taylor Swift entitled “Taylor Swift’s Songwriting Process on evermore”. The theory used to answer the two research problems was Brown & Levinson (1987), and the qualitative method was used as the research method. The result indicates that there are 41 utterances containing politeness strategies, which are divided into 1 bald on record, 30 positive politeness, 9 negative politeness, and 1 off record. The strategy found in bald on record is no face threat minimization. Furthermore, it was found that Zane and Taylor used various sub-strategies of positive politeness, which consist of 6 exaggerating, 8 giving gifts to the hearer, 8 presupposing, raising, and asserting common ground, 1 including S and H in the activity, 1 be optimistic, 1 intensifying interest to the hearer, 2 joking, 2 noticing, attending to the hearer, and 1 seeking agreement. For negative politeness, the sub-strategies used are 7 questions and hedge and 2 apologize. Finally, for off record, use contradictions. Therefore, the most dominant strategy is positive politeness with the sub-strategy of giving gifts to the hearer and presupposing, raising, and asserting common ground. Furthermore, it was found that payoff and social distance are two factors that influence the use of politeness strategies. The payoff factor appears in 40 utterances and social distance 4 utterances. Thus, it can be stated that Zane and Taylor want to establish a friendly, relaxed, and positive conversation and strengthen closeness. The payoff factor also implies that both want to satisfy each other’s face.